PENGEMBANGAN LKS KONTEKSTUAL SUB MATERI PERAN TUMBUHAN DI BIDANG EKONOMI UNTUK PEMBUATAN COOKIES PISANG - Ramadhan, Ramadhan; Daningsih, Entin; Yokhebed, Yokhebed (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aimed to know feasibility and studentsâ€™ response to contextual student worksheet for laboratory work of making banana cookies on submaterial plant role in economy. The type of research was type of research and development (R&D), which consisted of six stages namely potential and problems, data collection, design production, validation of design, revision of design, and limited product trial. Data collection was done by literature review and implemented organoleptic test on three types of banana cookies. Contextual student worksheets contained submaterial plant role in economy with the example of banana cookies recipe. The banana recipe was made from 40 hari banana selected from significant parameter of organoleptic test. To know feasibility of contextual student worksheet, then validation was done by two lecturers of Biology Education FKIP Untan and three biology teachers of class X senior high school. Aspects of feasibility measured in validation were content, linguistic, display, graphic, and contextual. Result of validation showed 0.99 of CVI value and categorized valid, so it was veasible to use learning material. The results of this study also showed students' responses to contextual student worksheets was as much as 85.74% with very high categories.Â Keyword: Banana Cookies, Contextual Student Worksheet, Feasibility, Research and Development Method, and Responses.Â